Perubahan Tutupan Lahan Terbangun di Kota Pekanbaru Tahun 2000-2022 - Muhammad Ilyas Nizar; Irland Fardani (UNISBA Press, 2023)
Abstrak.Pekanbaru City is the Capital City of Riau Province, where many economic activities occur in Pekanbaru City. As a result of these activities it will cause population growth which causes an increase in built-up land due to the attraction in the form of jobs to come to Pekanbaru City. It is feared that population growth will lead to a less regular pattern of development of the built-up land cover and can cause inconvenience to living in the area. Based on the background that has been described, the formulation of the problem in this study is as follows: